Perceptions of chemoprevention among individuals at high risk of oral cancer: qualitative study within the UK-based SAVER trial - Bridget Young; J Perry; Caroline McCarthy; Stefano Fedele; R Shaw; Frances Sherratt; Albert Jiménez-Tomàs; R Kuruvilla; M W Ho; M Daunt; S Moorhouse (BMJ Open)
Objectives Clinical trials are needed to advance interventions such as chemoprevention that have potential to reduce the risk of malignant transformation in individuals with oral potentially malignant disorders. We explored the perspectives of those screened or invited to join an early phase clinical trial (the SAVER trial: Sodium valproate for the epigenetic reprogramming of high-risk oral epithelial dysplasia). Our objectives were to inform the SAVER trial while it was ongoing and to provide insights for future trials and chemoprevention therapy development more broadly.Design Qualitative study involving audio-recorded, semistructured interviews. Analysis of transcribed interviews drew on thematic approaches.Setting Five UK-based sites involved in SAVER.Participants Purposive sample of individuals (n=20) with suspected or diagnosed oral epithelial dysplasia (OED) who were approached about SAVER.Results Most interviewees readily accepted that OED warranted preventive treatment and were positive about the potential of chemoprevention. However, they were often concerned about the side effects of the trial medication, and together with a dislike of biopsies and a perception that the trial might disadvantage treatment, these concerns made some hesitant to participate in SAVER. Interviewees indicated that the communication of staff influenced their understanding and experience of the trial and identified several opportunities for enhancing these aspects.Conclusions In indicating that individuals at risk of malignant transformation are accepting of chemoprevention in principle, our findings are supportive of future research on chemoprevention for this group. The findings also draw attention to the crucial role of communication in recruitment to chemoprevention trials. We provide recommendations to support staff during recruitment and enhance individuals’ experience of the trial.Trial registration number ISRCTN12448611; Pre-results.